BEETROOT PRETREATED BY FREEZE-THAW, AS A SOURCE OF NITRITES IN ITALIAN SALAMI ENRICHED WITH ALTERNATIVE PROTEINS (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
Fermented dried sausages are an ancient method of meat preservation in Europe. To enhance maturation and microbiological parameters, nitrites are added to salami. Fresh beet (Beta vulgaris L. var. conditiva Alef.) is a stable source of nitrates, containing them up to 1240 mg/kg. Sustainable drying of beet, involving freeze-thaw pretreatment and solar energy, is a climate-neutral solution for the food industry. However, beet pretreated by freeze-thaw is not used as a nitrite source in Italian salami with alternative proteins. Dried snails (Lissachatina fulica) and pumpkin seed protein isolate (Cucurbita pepo var. styriaca) were used to enrich salami. Both alternative proteins were added to recipes in equal amounts of 5%. Regular dried beet is commonly used as a colorant, but its nitrite-replacing properties are overlooked. Five salami samples enriched with alternative proteins were prepared: Control 1 (without nitrite/nitrate), Control 2 (125 mg/kg sodium nitrite and 125 mg/kg sodium nitrate), A1 (1% beet powder), A2 (1.5% beet powder), and A3 (2% beet powder). The best sample was A2, containing 1.5% beet powder and 5% dried snails and pumpkin seed protein. In A2, moisture content in raw salami was 64.7%, in fermented salami 34.5%, and the yield was 69.8%. Control 2 showed higher values (67.3%, 38.7%, 71.4%), but lower than Control 1. The highest organoleptic scores were in Control 2 (9.15) and A2 (9.2). The best taste (9.2) and aroma (9.6) were found in Control 2, while A2 had the best color (9.3) and texture (9.4). After 40 days of fermentation, aerobic mesophilic bacteria counted 9.7 log CFU/g across experimental samples, higher than Controls 1 and 2. Lactic acid bacteria were highest in A2 at 10.4 log CFU/g. Coliforms were below 3 MPN/g in all samples. After 60 days of storage, starter culture counts decreased by 10-15%, while coliforms remained below 3 MPN/g. Italian salami enriched with alternative proteins can be consumed in households, restaurants, and festivals. Future research should explore new beet varieties, analyze color parameters, and use beet powder in other meat recipes.
Keywords: European cuisine; meat products; alternative protein; zero hunger; healthy diet